Autonomous Technology in Scenario By Rare Geophysical Processes (Underwater Focus) (Global Journal of Science Frontier Research, 2022)
From an ecological perspective scientific investigation of the Earth system reveals its complexity evidenced by the interaction of geophysical processes which occur in the global atmospheric system in the world ocean both favoring the world climate in the interior of the globe and between each of these parts and outer space Environmental risks
Keywords: autonomous technology; underwater vehicle; earth system; deterministic chaos; geophysical processes; scenario; war games